2017
DOI: 10.1371/journal.pntd.0005830
|View full text |Cite
|
Sign up to set email alerts
|

Leptospira interrogans causes quantitative and morphological disturbances in adherens junctions and other biological groups of proteins in human endothelial cells

Abstract: Pathogenic Leptospira transmits from animals to humans, causing the zoonotic life-threatening infection called leptospirosis. This infection is reported worldwide with higher risk in tropical regions. Symptoms of leptospirosis range from mild illness to severe illness such as liver damage, kidney failure, respiratory distress, meningitis, and fatal hemorrhagic disease. Invasive species of Leptospira rapidly disseminate to multiple tissues where this bacterium damages host endothelial cells, increasing vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 87 publications
0
33
0
2
Order By: Relevance
“…A recent study by Sato and Coburn 33 showed that the most important finding seen in L. interrogans was the disruption of adherens junctions due to protein alterations. VE-cadherins, p120 catenin, alpha and beta catenins are specifically involved in the process.…”
Section: Cadherinsmentioning
confidence: 99%
“…A recent study by Sato and Coburn 33 showed that the most important finding seen in L. interrogans was the disruption of adherens junctions due to protein alterations. VE-cadherins, p120 catenin, alpha and beta catenins are specifically involved in the process.…”
Section: Cadherinsmentioning
confidence: 99%
“…The dermal human microvascular endothelial cell line (HMEC‐1) was acquired and grown as described previously (Sato & Coburn, ). To use HMEC‐1 for protein binding tests, cells were seeded at 4.8 × 10 5 per well on sterile coverslips placed in wells of 12‐well plates for 2‐day growth.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, antibodies against VE-Cadherin have been known to induce vascular permeability in mice, potentially to the point of haemorrhage (Corada et al, 1999), a phenomenon also observed during leptospirosis (Plank & Dean, 2000). Furthermore, pathogenic, but not saprophytic, Leptospira have been shown to interrupt cell-to-cell junctions in vitro (Sato & Coburn, 2017). Enhanced vascular permeability facilitated by LIC10831 may allow the bacterium to escape host blood vessels to take up residence in preferred host tissues (Barnett et al, 1999;Ozuru et al, 2017).…”
Section: Lic10831 Also Binds Human Ve-cadherinmentioning
confidence: 99%
See 1 more Smart Citation
“…Un défaut de reconnaissance du lipopolysaccharide des spirochètes par les défenses innées de l'organisme, et en particulier par le Toll Like Receptor 4 (TLR4) chez l'humain serait impliqué dans la réponse insuffisante de l'hôte (Werts et al 2001). Les leptospires ont un tropisme particulier pour le foie, les reins, l'endothélium vasculaire et les poumons (Sato & Coburn, 2017). L'infection induit alors une réponse inflammatoire particulièrement forte avec libération de grande quantité de cytokines pro-inflammatoires et une forte élévation de la protéine C réactive (CRP).…”
Section: Physiopathologieunclassified